Protection of tooth structure by chlorhexidine and natural polyphenols: a review - Pilly, Vinay; Lacerda Brito Junior, Carlos Henrique; Rocha Nogueira Filho, Getulio; Prakki, Anuradha (Brazilian Dental Science, 2012)
Caries is a multifactorial and transmittable disease that results mainly from bacteria present in the oral cavity. Oral microorganisms can produce metabolic acids that diffuse through dental tissues and interfaces leading to dissolution of mineral. In dentine, after mineral is dissolved, organic matrix is also exposed to breakdown by host enzymes such as matrix metalloproteinases (MMPs) that are activated by low pH followed by neutralization. This review aims to discuss the activity of different antibacterial and antiproteolytic compounds such as chlorhexidine and natural polyphenols in the control of caries progression.Keywords: chlorhexidine, catechin, polyphenol, caries, dentine